(untitled) (Journal of the Bangladesh Agricultural University, 2011)
Experiment was carried out in the mushroom cultivation laboratory, Horticulture Center, Khairtala, Jessore to evaluate the better performance of oyster mushroom Pleurotus florida in different substrate compositions as well as to find out the better substrate for mushroom cultivation. Highest mycelium running rate was found in banana leaves and rice straw (1:1) but the lowest in control. Completion of mycelium running time was lowest in banana leaves and rice straw (1:3 and 3:1). Number of total primordia and effective primordia, found highest in control but the maximum pileus thickness was measured from rice straw. Highest biological yield and economic yield (164.4 g and 151.1 g) was obtained from rice straw which was much higher than control. From the graphical view, both positive and negative relationships were found between economic yield and different yield contributing attributes. Keywords: Banana leaves; Rice straw; Growth; Yield; Pleurotus florida DOI: 10.3329/jbau.v8i2.7928 J. Bangladesh Agril. Univ. 8(2): 213-220, 2010